PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL MEREK CHEVROLET CAPTIVA - Erwin Dwi Purnawan; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The development of the automotive industry in Indonesia has grown rapidly, with the number of vehicle manufacturers in Indonesia currently making consumers have many choices before deciding which car to buy. In 2014-2016 Chevrolet Captiva can not achieve sales targets. Chevrolet Captiva should still have a chance to reach the target. Chevrolet should strive to know what the consumer wants and needs, Chevrolet should figure out what factors are affecting in making purchasing decisions.This study aims to determine the effect of product quality and service quality variables on Chevrolet Captiva purchase decisions on Chevrolet Semarang consumers.Type of this research is explanatory with 45 respondents were taken with purposive sampling technique. Data collection techniques used questionnaires and interviews. Data analysis technique used in this research is regression analysis with SPSS software (Statistical Product and Service Solutions) version 20.0.The results showed that product quality has an effect on purchasing decision with correlation coefficient 0,591 and coefficient of determination 35%, Service quality has an effect on purchasing decision with correlation coefficient 0,621 and coefficient of determination 38,6%. Product quality and service quality together have influence to purchase decision with equation Y = 4,362 + 0,199 X1 + 0,317 X2. It means the more influential product quality and service quality will increase purchasing decisions.The conclusion of research is product quality and service quality influence to purchasing decision. The advice given to the company is to strengthen product quality and re-evaluate the quality of its services.